2019
DOI: 10.22401/anjs.22.4.02
|View full text |Cite
|
Sign up to set email alerts
|

Study of Some Biochemical Parameters in Epileptic Patients

Abstract: Epilepsy is a worldwide disease characterized by huge changes in several biochemical parameters due to seizure the main symptoms of the disease. The aim of this study was to assess some biochemical parameters in epileptic patient. This study involves 31 patients with 31 healthy as a control group for each one of both groups, the following parameters were assessed: {8hydroxydeoxy guanosine(8-OHdG), Malondialdehyde (MDA), Prolactin, Lactate dehydrogenase (LDH), Albumin, Total bilirubin (TSB), Alkaline phosphatas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…On the hand some specific proteins were studied such as haptoglobin an referred to participate in generalized epilepsy with idiopathic [28]. Insignificant decrease in bilirubin was obtained in the study whereas Ibrahim and Alhashemi [29] found a significant decrease. The reason may be due to bilirubin acts as an antioxidant function that can prevent the oxidation of fats, and it is affected by epilepsy patients [30].…”
Section: Resultsmentioning
confidence: 99%
“…On the hand some specific proteins were studied such as haptoglobin an referred to participate in generalized epilepsy with idiopathic [28]. Insignificant decrease in bilirubin was obtained in the study whereas Ibrahim and Alhashemi [29] found a significant decrease. The reason may be due to bilirubin acts as an antioxidant function that can prevent the oxidation of fats, and it is affected by epilepsy patients [30].…”
Section: Resultsmentioning
confidence: 99%